2010
DOI: 10.1371/journal.pone.0011227
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of the Recurrence of Anaemia in Gambian Children Following Discharge from Hospital

Abstract: BackgroundIn malaria endemic countries, children who have experienced an episode of severe anaemia are at increased risk of a recurrence of anaemia. There is a need to find ways of protecting these at risk children from malaria and chemoprevention offers a potential way of achieving this objective.MethodsDuring the 2003 and 2004 malaria transmission seasons, 1200 Gambian children with moderate or severe anaemia (Hb concentration <7 g/dL) were randomised to receive either monthly sulfadoxine-pyrimethamine (SP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 33 publications
(37 reference statements)
1
48
0
Order By: Relevance
“…All included trials were conducted in malaria‐endemic areas. Three trials were conducted in low endemicity areas: two in The Gambia ( Bojang 2010 GMB ; Cox 2013 GMB ) and one in eastern Kenya ( Verhoef 2002 KEN ). Three trials were conducted in high endemicity areas: one in western Kenya ( Desai 2003 KEN ), one in southern Malawi ( Phiri 2012 MWI ) and one in western Tanzania ( Tomashek 2001 TNZ ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All included trials were conducted in malaria‐endemic areas. Three trials were conducted in low endemicity areas: two in The Gambia ( Bojang 2010 GMB ; Cox 2013 GMB ) and one in eastern Kenya ( Verhoef 2002 KEN ). Three trials were conducted in high endemicity areas: one in western Kenya ( Desai 2003 KEN ), one in southern Malawi ( Phiri 2012 MWI ) and one in western Tanzania ( Tomashek 2001 TNZ ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining trial enrolled children with Hb levels less than 7 g/dL ( Bojang 2010 GMB ). In one trial, children had severe malaria ( Phiri 2012 MWI ), two trials included children with uncomplicated malaria ( Cox 2013 GMB ; Desai 2003 KEN ), for two trials malaria was not part of the inclusion criteria ( Bojang 2010 GMB ; Tomashek 2001 TNZ ) and one trial excluded children with clinical malaria ( Verhoef 2002 KEN ). Three trials ( Bojang 2010 GMB ; Phiri 2012 MWI ; Tomashek 2001 TNZ ) recruited children that attended outpatient clinics or were admitted to hospital, while three trials recruited children from the community ( Cox 2013 GMB ; Desai 2003 KEN ; Verhoef 2002 KEN ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other trials have demonstrated increased adverse effects (27) , including increased hospital admissions (23) . Other useful measures assessed for reducing anaemia included malaria control (20,28,29) , anthelmintics (30) especially albendazole-praziquantel combinations (16) , daily micronutrients (5,31) and delayed cord clamping (32) . Food fortification with micronised Fe improved children's Fe stores but did not increase Hb levels (2,33) .…”
Section: Preventionmentioning
confidence: 99%